The influence of discovery learning model using loose parts-based media on early childhood critical thinking abilities - Savitri, Tiara Nur; Pradana, Pascalian Hadi; Hasanah, Hisbiyatul (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: The implementation of the independent curriculum in modern education is a breakthrough aimed at improving the quality of education in Indonesia. This curriculum is expected to enhance students' quality in various areas, one of which is the development of critical thinking skills in early childhood.Aim: This research aims to determine the effect of the discovery learning model using loose parts media on the critical thinking skills of early childhood.Method: This quantitative research involves 5-6-year-old students at Pos Paud Tanjung as the sample. Data collection was conducted through observation using a one-group pretest-posttest research design. The data analysis technique employed statistical testing using the T-test.Results: The results of the data analysis indicate that there is an effect of the discovery learning model using loose parts media on the critical thinking skills of early childhood, as evidenced by a significance result of 0,01 < 0,05 and a negative t-value of -15,657 < -2,10982. The average critical thinking skills score of the children before the treatment was 5,77.Conclusion: Thus, these findings contribute to the understanding of the potential application of the discovery learning model using loose parts-based media in enhancing the critical thinking skills of early childhood.